(untitled) (Oxford, 2008)
Trans fatty acids (TFAs) have long been used to make fats and fat blends more attractive to consumers. However, research has shown TFAs can increase bad blood cholesterol levels while reducing the good. As consumers become more savvy many manufacturers and retailers are now obliged to reduce or eliminate TFAs in the finished product and find alternatives. This collection of nine articles gives researchers and students a good grounding in the science behind TFAs, including their structure, occurrence, nomenclature, biosynthesis and properties, along with information on the epidemiology and health implications of fatty acids, the effects of conjugated linoleic acids on body composition and clinical biomarkers of disease, analysis of trans monounsaturated and polyunsaturated fatty acids, the control of physical and chemical properties of fat blends, trans isoner control in the hydrogenation of edible oils, fractionation and interesterification, fixed applications of FTAs and food products without trans fatty acids
Keywords: Trans fatty acids,Axít béo